Co‐conformational Exchange Triggered by Molecular Recognition in a Di(acylamino)pyridine‐Based Molecular Shuttle Containing Two Pyridine Rings at the Macrocycle. Issue 12 (21st January 2016) - Martinez‐Cuezva, Alberto; Carro‐Guillen, Fernando; Pastor, Aurelia; Marin‐Luna, Marta; Orenes, Raul‐Angel; Alajarin, Mateo; Berna, Jose
Abstract: We describe the incorporation of endo ‐pyridine units into the tetralactam ring of di(acylamino)pyridine‐based rotaxanes. This macrocycle strongly associates with the linear interlocked component as confirmed by X‐ray diffraction studies of rotaxane2 b . Dynamic NMR studies of2 b in solution revealed a rotational energy barrier that was higher than that of the related rotaxane2 a, which lacks of pyridine rings in the macrocycle. The macrocycle distribution of the molecular shuttle4 b, containing two endo ‐pyridine rings, shows that the major co‐conformer is that with the cyclic component sitting over the di(acylamino)pyridine station. DFT calculations also support the marked preference of the ring for occupying the heterocyclic binding site. The association of N ‐hexylthymine with the di(acylamino)pyridine binding site of4 b led to the formation of a rare 'S'‐shaped co‐conformer in which the tetralactam ring interacts simultaneously with both stations of the thread. Abstract : Sticky rings ! Rotational and translational internal motions of di(acylamino)pyridine rotaxanes containing dipyridine‐based rings are examined. The association of one of these interlocked compounds and a derivate of thymine leads to the formation of a stable 'S'‐shaped co‐conformer.